Peningkatan Hasil Belajar Pendidikan Pancasila Berbantuan Canva Dengan Model Two Stay Two Stray di Sekolah Dasar - Aini, Qurrota; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research aims to describe the improvement in student learning outcomes in Canva-assisted Pancasila Education learning with the Two Stay Two Stray Cooperative Learning model for class IV students at SD Negeri 06 Pulai Anak Air, Bukittinggi City. The research used is a type of classroom action research (PTK) using qualitative and quantitative approaches. The subjects of this research were 26 class IV teachers and students. Data collection techniques include observation, tests and non-tests. This research was carried out in 2 cycles, in each cycle there were 4 stages, namely planning, implementation, observation and reflection. The results of the research showed an increase, in the first cycle the teaching module obtained an average of 84.69% and in the second cycle it was 94.44%. The first cycle teacher aspect obtained an average of 82.14% and the second cycle was 96.42%. Aspect of students in cycle I obtained an average of 80.35% and in cycle II it was 96.42%. Student learning outcomes in cycle I obtained an average of 77.78% and in cycle II it increased to 90.5%. Thus, it can be concluded that the Two Stay Two Stray Cooperative Learning model assisted by Canva can improve student learning outcomes in Pancasila education learning.